Analisis Kestabilan Lereng Metode Morgenstern-Price Jalan Poros Malino - Sinjai Kabupaten Gowa - Hedianto Hedianto; A Al'faizah Ma'arief; Enni Tri Mahyuni (Jurnal Geomine, 2022)
Malino-Sinjai Road, Gowa Regency is an area that is prone to landslides in the rainy season, where the geological condition is in the form of Baturape-Cindako Volcano unit, namely volcanic rock of Pliocene. The research location is located on Malino-Sinjai Road Km ± 54 Parangloe District and Km ± 71 Tinggi Moncong District, Gowa Regency, the average slope of the study area is 45 °. The purpose of this research is to conduct geological engineering observations on the slopes in the form of lithological conditions, and discontinuous areas on the slopes. Conduct slope stability analysis using software using the Morgenstern-Price method, and provide technical or design recommendations for the observed slope conditions. The research methodology uses primary data, namely data from observations of engineering geology and geometry of the slopes, as well as secondary data in the form of data from previous studies, books and also the results of laboratory tests of physical and mechanical properties of rocks. The results of the study obtained technical geological observation data that on the slope (A) which is located on Malino-Sinjai Road Km ± 54 Parangloe District in the form of basalt rock has a high level of weathering characterized by an average joint distance of 9 cm and the condition of the top of the slope area has been become residual soil, while on the slope (B) which is located on Malino-Sinjai Road Km ± 71 Kecamatan Tinggi Moncong in the form of tuff rock, the level of weathering is still in the mildly weathered category and the solid condition is not visible. Based on the results of interpretation using the Morgenstern-Price method, the slope safety factor value (A) is FK 1.101 which is considered unstable based on the minimum standard of slope safety factor of the Ministry of Public Works in 2014 which is 1.25. On the slope (B) the safety factor value is obtained, namely FK 1.371, where the slope is considered stable or safe. As for technical or design recommendations to prevent ground shaking, the slope (A) can use retaining walls or retaining walls and for slopes (B) use wire mesh or wire nets around the observation slope.